Rational Design of Superior Electrocatalysts for Water Oxidation: Crystalline or Amorphous Structure?. Issue 9 (3rd August 2021) - Guan, Daqin; Zhou, Wei; Shao, Zongping
Abstract : Crystalline, amorphous, and crystalline–amorphous materials have become three important electrode materials for the bottleneck oxygen‐evolving reaction (OER) in the promising hydrogen‐producing technology of water splitting. With the rapid development of in situ/ex situ characterizations, the understanding of active sites in electrocatalysts has been deepened via the structure–activity/stability relationships extracted from the observations on catalysts during/after the OER. Herein, the origins of changes in initial crystalline, amorphous, and crystalline–amorphous materials during/after the OER are systematically analyzed and the underlying variation effects on catalyst activity and stability are discussed based on recent representative studies, aiming at guiding OER catalyst design in the future. Abstract : Crystalline, amorphous, and crystalline–amorphous materials have been explored for catalyzing the oxygen‐evolving reaction (OER). However, a systematic insight into the origins and effects of the behaviors on initial crystalline, amorphous, and crystalline–amorphous materials during/after the OER is still absent. Herein, it is attempted to offer a systematic viewpoint on these issues to guide the rational design of electrocatalysts.